Endoplasmic Reticulum Chaperone GRP78 Protects Heart From Ischemia/Reperfusion Injury Through Akt Activation. Issue 11 (25th May 2018) - Bi, Xukun; Zhang, Guangyu; Wang, Xiaoding; Nguyen, Chau; May, Herman I.; Li, Xiaoting; Al-Hashimi, Ali A.; Austin, Richard C.; Gillette, Thomas G.; Fu, Guosheng; Wang, Zhao V.; Hill, Joseph A.
Abstract : Rationale: : Restoration of coronary artery blood flow is the most effective means of ameliorating myocardial damage triggered by ischemic heart disease. However, coronary reperfusion elicits an increment of additional injury to the myocardium. Accumulating evidence indicates that the unfolded protein response (UPR) in cardiomyocytes is activated by ischemia/reperfusion (I/R) injury. Xbp1s (spliced X-box binding protein 1), the most highly conserved branch of the unfolded protein response, is protective in response to cardiac I/R injury. GRP78 (78 kDa glucose-regulated protein), a master regulator of the UPR and an Xbp1s target, is upregulated after I/R. However, its role in the protective response of Xbp1s during I/R remains largely undefined. Objective: : To elucidate the role of GRP78 in the cardiomyocyte response to I/R using both in vitro and in vivo approaches. Methods and Results: : Simulated I/R injury to cultured neonatal rat ventricular myocytes induced apoptotic cell death and strong activation of the UPR and GRP78. Overexpression of GRP78 in neonatal rat ventricular myocytes significantly protected myocytes from I/R-induced cell death. Furthermore, cardiomyocyte-specific overexpression of GRP78 ameliorated I/R damage to the heart in vivo. Exploration of underlying mechanisms revealed that GRP78 mitigates cellular damage by suppressing the accumulation of reactive oxygen species. We go on to show that the GRP78-mediated cytoprotective response involves plasma membrane translocation of GRP78 and interaction with PI3 kinase, culminating in stimulation of Akt. This response is required as inhibition of the Akt pathway significantly blunted the antioxidant activity and cardioprotective effects of GRP78. Conclusions: : I/R induction of GRP78 in cardiomyocytes stimulates Akt signaling and protects against oxidative stress, which together protect cells from I/R damage. Abstract : Supplemental Digital Content is available in the text.